Pengaruh Promosi, Customer Rating, dan Kualitas Produk Terhadap Keputusan Pembelian Pada Tiktok Shop di Kota Batam - Danu Wiranda; Winda Evyanto (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study was designed to examine in depth the role of promotion, customer rating, and product quality in shaping consumer purchasing decisions for Lentiven powerbank products marketed through the TikTok Shop platform in Batam City. The study used a quantitative approach with a descriptive design, where respondents were determined through a purposive sampling technique, namely consumers who had purchased and used Lentiven powerbanks. The determination of the sample size referred to Lemeshow's calculations, resulting in 100 respondents who were considered capable of representing the study population. Data collection was carried out using a questionnaire instrument, which was then analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the multiple linear regression analysis can show that promotion has an influence of 22.2%, customer rating contributes 36.3%, and product quality has an influence of 29.0% on purchasing decisions. The results of the coefficient of determination (R2) analysis show that promotion, customer rating, and product quality are able to explain 75.3% of the variation in purchasing decisions, while the rest is influenced by other factors. The t-test and F-test findings confirm that promotion, customer rating, and product quality are strategic factors that play a significant role, both partially and simultaneously, in driving the purchase decision for Lentiven power banks at TikTok Shop in Batam City.